At-School Victimization and Violence Exposure Assessed in a National Household Survey of Children and Youth. (2nd January 2016) - Finkelhor, David; Vanderminden, Jennifer; Turner, Heather; Shattuck, Anne; Hamby, Sherry
Abstract : This national household telephone survey of youth and parents assessed exposure to a broad range of at-school victimizations among a representative sample of 3, 391 children and youth ages 5 to 17. Nearly half the sample (48%) had been exposed to at least one form of victimization at school during the past year (in 2011), most of which was intimidation/bullying (29.8%). Fourteen percent had been assaulted at school in the past year, 13% had witnessed an assault, 3.2% had been sexually harassed, and 0.4%, had been sexually assaulted at school. Twelve percent had an at-school victimization injury in the past year, and 6% had missed a day or more of school as a result of their at-school victimization. Some victimizations, such as weapon assault and sexual assault, were less prevalent at school than out of school, others, such as intimidation and sexual harassment, were more common.